(untitled) (Global Journal of Management and Business Research, 2013)
The most important consideration for Western firms doing business in underdeveloped nations is political risk. Experts argue that political risk is any threat to the long run profitability of the company’s operations which grows not from the normal economic functioning of a society, but rather from nationalistic discriminatory actions of host countries. The pressure which might cause government to act in a manner adverse to the interest foreign investors in Africa may be viewed as falling into three categories namely; arising from system instability, those arising from resentment of foreign investment, those arising form conflict with perceptions of host country’s national interests. Interference is not necessarily always the result of antagonism to foreign investment. Balance of payment, monetary and fiscal problems can at time bring about restrictive actions that affect foreign and domestic businesses alike. This paper is focused on analyzing the cause of political risks facing multinational corporations in under-developed nations.